2009
DOI: 10.1093/jac/dkp159
|View full text |Cite
|
Sign up to set email alerts
|

Nasal decolonization of Staphylococcus aureus with mupirocin: strengths, weaknesses and future prospects

Abstract: Staphylococcus aureus in the nose is a risk factor for endogenous staphylococcal infection. UK guidelines recommend the use of mupirocin for nasal decolonization in certain groups of patients colonized with methicillin-resistant S. aureus (MRSA). Mupirocin is effective at removing S. aureus from the nose over a few weeks, but relapses are common within several months. There are only a few prospective randomized clinical trials that have been completed with sufficient patients, but those that have been reported… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
108
0
4

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 149 publications
(113 citation statements)
references
References 82 publications
1
108
0
4
Order By: Relevance
“…[10][11][12][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31]33 Nasal mupirocin is considered the best topical agent for the eradication of gram-positive bacteria immediately following the treatment, when the adherence to this protocol is high. 35 As shown in chart 1, 68.8% of the studies that used topical mupirocin for patient decolonization achieved an effective outcome. 12,[14][15][16][19][20]22,25,31,33 Corroborating this result, it is found that topical treatment using mupirocin is indicated by most international health guidelines, including those of the CDC and WHO.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…[10][11][12][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31]33 Nasal mupirocin is considered the best topical agent for the eradication of gram-positive bacteria immediately following the treatment, when the adherence to this protocol is high. 35 As shown in chart 1, 68.8% of the studies that used topical mupirocin for patient decolonization achieved an effective outcome. 12,[14][15][16][19][20]22,25,31,33 Corroborating this result, it is found that topical treatment using mupirocin is indicated by most international health guidelines, including those of the CDC and WHO.…”
Section: Discussionmentioning
confidence: 99%
“…35 Poor adherence can be avoided by making the nursing team or research professionals accountable for conducting the decolonization, or by establishing a protocol supervision scheme, as reported in many of the analyzed studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the UK, it is recommended that MRSA carriers who are receiving prophylaxis for an operation should undergo nasal decolonization with mupirocin, the most commonly used antibiotic for Grampositive bacteria [6]. Because nasal relapses are common within several months [7], and mupirocin resistant S. aureus strains have recently been reported [8], alternate treatments are being pursued by various groups.…”
Section: Introductionmentioning
confidence: 99%